THE DIGITAL TRINITY: INFLUENCERS, REVIEWS AND BRAND – QUANTIFYING THEIR SYNERGISTIC EFFECT ON FNB PURCHASE INTENTION - Muhammad Sa`ad Trisnawijaya; Evi Jayanti Yonardi; Anastasya Putri Haeruddin; Denny Eka Axelito; Denis Hartanto; Erwin Erwin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Trends in social media marketing have advanced significantly and are being utilized by culinary business operators. These trends are used to build Brand Awareness, which increases consumers' Purchase Intention. The purpose of this study is to analyze the effect of Influencer Marketing and Online Customer Reviews on Purchase Intention, with the mediating role of Brand Awareness. This study was analyzed using Partial Least Squares Structural Equation Model (PLS-SEM). The collected data were then processed using SMART-PLS. A total of 160 consumers from the Gen Z and Y demographics were surveyed using questionnaires with a 5-point Likert scale. The study shows that Online Customer Reviews can influence Purchase Intention, unlike Influencer Marketing, which only affects Purchase Intention through Brand Awareness. This highlights the central role of Brand Awareness for every trend used, which, in this case, Influencer Marketing and Online Customer Reviews contribute to purchase intention. Therefore, operators in the culinary business must aim to balance the use of existing trends with efforts to enhance their Brand Awareness.